ANALISIS BUMD (PDAM TIRTA KHATULISTIWA DAN BPR KHATULISTIWA) TERHADAP PAD KOTA PONTIANAK TAHUN 2016-2019 - Zulka Sapta Dilla; Nindy Puspitasari (Jurnal Ekonomi STIEP, 2023)
ABSTRACT "Analysis of Regional Owned Enterprises (BUMD) on Regional Original Income (PAD) for Pontianak City" is a source of funding for the development and maintenance of the Pontianak City area. As for the Regional Owned Enterprises in Pontianak City, which we have seen, there are only 2 BUMDs, namely PDAM Tirta Khatulistiwa and BPR Equator Pontianak. The author's research objective is to find out the contribution of BUMD profits to local revenue in Pontianak City in 2016-2019. The research method uses descriptive quantitative research which is analytical and calculating with data sources obtained from the BKD of Pontianak City and the Secretariat of the Mayor of Pontianak City. Based on the results of the study, it can be concluded that Contribution and Regional Original Income, namely the Profit Contribution of SOEs, especially to PDAM Tirta Khatulistiwa, is 2.53% of the total PAD, while at BPR Khatulistiwa Pontianak it is 0.19% of the Regional Original Revenue of Pontianak City, which is very small when compared to the other. So that efforts and innovations are needed to increase the revenue and contribution of BUMD, especially PDAM Tirta Khatulistiwa and BPR Khatulistiwa Pontianak to PAD Pontianak City.